The Kingdom Focused Leader : Seeing God at Work in you through you, & around You - Miller, Michael D. (Broadmen & Holman Publishers, 2004)
In his book, The Kingdom-Focused Church, Gene Mims set the vision for the church to catch a new passion for Jesus that would seep into every crevice of the lives of its members. The resulting revival would fuel the revitalization of the Kingdom of God in the world. Now, Michael Miller writes to those who are charged with lighting the path for individuals and organizations seeking to become kingdom-focused. The Kingdom-Focused Leader recognizes on Jesus Christ as the consummate leader of all time—as a leader focused on the Kingdom of God in His earthly ministry; as the one who continues His leadership in guiding God's people to advance the Kingdom of God throughout the world. Miller explains how every leader can model Jesus' example of constant awareness that the Kingdom of God works in, through, and around all Christians.